Summary of Best Evidence for Integrated Airway Management in ICU Tracheostomy Patients - Guo J; Li Y; Xie D; Zhang M; Fu S (Journal of Multidisciplinary Healthcare)
Jixiang Guo,1,2 Yiwen Li,1,2 Dongxue Xie,1,2 Mingyang Zhang,1 Simao Fu3 1Department of Surgical Anesthesiology-Division 1, Zhongshan People’s Hospital, Zhongshan City, Guangdong Province, 528403, People’s Republic of China; 2School of Nursing and Health, Henan University, Kaifeng City, Henan Province, 475004, People’s Republic of China; 3Dean’s Office, Zhongshan People’s Hospital, Zhongshan City, Guangdong Province, 528403, People’s Republic of ChinaCorrespondence: Simao Fu, Dean’s Office, Zhongshan People’s Hospital, 2 Sun Wen East Road, Zhongshan City, Guangdong Province, People’s Republic of China, Email 2059202645@qq.comObjective: The aim of this study was to comprehensively summarize the best currently available evidence by reviewing and analyzing the relevant literature in the area of care and maintenance of tracheostomy patients in the ICU. The evidence covers a wide range of aspects of postoperative care, complication prevention and management, rehabilitation support, and multidisciplinary collaboration for tracheostomy patients.Methods: Using the “ 6S” evidence-based model, we searched multiple databases. The search focused on evidence related to the care of tracheostomy patients, including maintenance, nursing measures, multidisciplinary collaboration, and quality improvement, with the time frame ranging from the inception of the databases to March 14, 2025. Two researchers independently evaluated the quality of the literature, extracted data, and summarized evidence from publications meeting the inclusion criteria.Results: A total of 12 relevant documents were retrieved, including 6 guidelines, 2 expert consensus papers, 1 best clinical practice guideline, 3 Meta-analyses. Through summarization and induction, 49 best evidence pieces were obtained across three major themes: maintenance and protection, nursing measures, and multidisciplinary collaboration and quality improvement. These were further divided into 15 sub-themes, covering equipment management, environmental optimization, infection prevention, postoperative care, airway humidification, suctioning, tracheostomy tube management, skin care, rehabilitation exercises, complication prevention, and daily assessments.Conclusion: This research systematically compiles the optimal evidence regarding the care and management of tracheostomy patients, offering a comprehensive foundation for evidence-based clinical practice. It assists healthcare professionals in developing personalized care plans, improving patient safety, reducing complications, and promoting recovery. Future research should focus on optimizing multidisciplinary collaboration, exploring nurse-led interventions, and addressing cultural and resource limitations to further enhance the standardization and personalization of tracheostomy care.Keywords: tracheostomy, care management, multidisciplinary collaboration, evidence summary, quality improvement, best practices